SUCCESSFUL USE OF DELAYED THERAPEUTIC PLASMA EXCHANGE IN SERONEGATIVE PEDIATRIC AUTOIMMUNE ENCEPHALITIS - Andric, Biljana; Ostojic, Slavica; Radonjic, Zorica; Serbic, Olivera; Kovacevic, Gordana; Vucetic-Tadic, Biljana; Ristic, Snezana; Kravljanac, Ruzica (Medical Research, 2025)
We present a 5-year-old girl with severe seronegative autoimmune encephalitis (AE) who was treated with therapeutic plasma exchange (TPE) after unsuccessful treatment with corticosteroids and intravenous immunoglobulins (IVIG). We performed 6 TPEs every other day in the Intensive Care Unit (ICU) using a Spectra Optia apheresis system and a central venous catheter for vascular access. We used a 5% albumin for substitution and acid-citrate dextrose-A (ACD-A) solution for anticoagulation. The exchange set was primed with allogenic compatible red blood cells because the patient weighed < 20kg. Before each TPE, we checked the patient’s blood count and coagulation status. A slow intravenous infusion of calcium gluconate (30mg/kg/h) was administered to maintain ionized calcium levels above 1 mmol/L/L. The mean inlet flow rate was 22.5 ± 4.1 ml/min, and the processed total blood volume was 2794.5 ± 106.0 ml. On average, 1243.2 ± 49.2 ml (1.55 ± 0.05) total plasma volume was exchanged, with 288.8 ± 13.8 ml of ACD used. The mean procedure duration time was 137.2 ± 9.2 min. After the third procedure, significant clinical improvement was observed in the girl. She smiled purposefully, followed with her gaze, and focused on the audiovisual content adapted for her age. Two weeks after the last TPE, the girl was discharged in good clinical condition from the hospital. Three years after the treatment, the patient was in good general condition with normal neurological status and without sequelae. This case highlights the therapeutic effectiveness of TPE, even when initiated late, in pediatric patients with severe AE.